Habitat modification as a means of restoring crested auklet colonies. Issue 1 (21st September 2016) - Major, Heather L.; Buxton, Rachel T.; Schacter, Carley R.; Conners, Melinda G.; Jones, Ian L.
ABSTRACT: Seabirds that forage in dense groups can be especially vulnerable to anthropogenic threats at sea. To mitigate these threats to populations, nesting habitat restoration may be a viable option by reducing negative density dependence. Accordingly, we undertook a before‐after control‐impact (BACI) experiment to test whether habitat modification could be an effective means of restoring nesting habitat of crested auklets ( Aethia cristatella ) breeding on Gareloi Island, Alaska, USA. Despite supporting large numbers of crevice‐nesting auklets, many lava flows at Gareloi Island are in a stage of late vegetative succession that may prevent birds from accessing subterranean nesting habitat. We hypothesized that crested auklet density is highest in unvegetated blocky and porous lava, and predicted that removing vegetation from the surface would allow new recruits to secure previously unavailable nesting sites. In 2009 and 2010, we delineated 34 200‐m 2 plots throughout the southeast colony at Gareloi, and color marked a subset of crested auklets landing in each plot to measure movement and abundance. We removed vegetative overgrowth and peat from half of each plot at the end of the 2009 (4 plots) and 2010 (30 plots) breeding seasons. Before and after vegetation removal, we counted the number of active nesting sites and calculated the ratio of banded to un‐banded breeders on the surface of each plot half. Overall, active nesting sites, number of individuals on the surface, and number of breeders landing did not increase after vegetation removal. However, among banded individuals that moved among plot halves, birds were 1.7 times more likely to move to a de‐vegetated plot half. Based on our experimental results, we found no evidence that vegetation removal increased crested auklet numbers at Gareloi Island, and thus in the short term this may not be a viable option for increasing crested auklet abundance. © 2016 The Wildlife Society. Abstract : Our study evaluated whether removing vegetative overgrowth from parts of an auklet colony would increase crested auklet abundance by increasing access to nesting habitat. We found that the removal of vegetation alone was not adequate to increase crested auklet abundance, and thus in the short term (3–4 years), vegetation removal may not be a viable option to mitigate anthropogenic mortality of auklets.